PERSPECTIVA DE EDUCADORES SOBRE O PROCESSO DE INCLUSÃO DE ALUNOS COM DEFICIÊNCIA FÍSICA E/OU MÚLTIPLA - Vidal, Laura da Rosa (2021)
undergoes changes in understanding, having evolved from an assistance model, going through a practice focused only on an interaction, until supported by the laws. In the last decades there has been a significant increase in the number of students with disabilities enrolled at all levels of education in Brazil, so it becomes important to identify a quality of access to the school environment, investigating which factors facilitate and which hinder their participation participation. Objective: To investigate how inclusive practices occur in state schools in the municipalities belonging to the 9th Education Coordination, from the perspective of educators. Methodology: The study was developed with teachers and managers from state elementary and high schools in the urban and rural areas of the municipalities of Boa Vista do Cadeado, Boa Vista do Incra, Cruz Alta, Fortaleza dos Valos, Ibirubá, Jacuizinho, Jari, Pejuçara , Quinze de Novembro, Salto do Jacuí and Tupanciretã, in Rio Grande do Sul (RS), in the period from September to October 2020. Participants responded to the survey through a questionnaire sent via the internet, which was composed of 10 questions multiple choice and an essay question. The study included 100 elementary and high school educators from the state network totaling 10% of the general population, of both sexes, who were included for convenience. Results: 100 teachers from a total of 1032 participated in the study, 69.1% of whom had a student with a physical disability, 57.1% had no undergraduate subjects related to how to work with inclusion in the classroom, 75.3 % have not received any training to work with students with physical disabilities in the last 5 years, 75.5% do not feel prepared to work with students with physical disabilities, 54.1% adapt the pedagogical resources for students with disabilities, 53 , 6% of teachers believe that the participation of the disabled student in the classroom is beneficial for everyone, 80.4% believe that their school has a commitment policy with the inclusion of their students. Conclusion: Inclusion in state schools in the municipalities belonging to the 9th CRE occurs through environments adapted to receive the disabled student, through the adaptation of resources in the classroom, and the school's commitment policy with the disabled student. The factors that facilitate the inclusion of students with disabilities in schools are adequate pedagogical resources, training of educators and adaptation of the physical environment of schools. In turn, the complicating factors are precisely the lack of facilitating factors, demonstrating that the availability of support services for educators and students with disabilities is insufficient.